2021
DOI: 10.1116/6.0001261
|View full text |Cite
|
Sign up to set email alerts
|

Applications of the National Institute of Standards and Technology (NIST) database for the simulation of electron spectra for surface analysis for quantitative x-ray photoelectron spectroscopy of nanostructures

Abstract: sessa (Simulation of Electron Spectra for Surface Analysis) is a software that was frequently used by the late Charles Fadley, since it provides a convenient means to simulate peak intensities as well as entire spectral regions for photoelectron spectroscopy. X-ray photoelectron spectra can be simulated for several types of nanostructures. sessa can also be utilized in more complex cases, e.g., if the nondipolar terms in the photoelectric ionization cross section need to be taken into account, a typical situat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…Regarding the NH-A ( Figure 14 ) and NH-B ( Figure 15 ) spectra, the presence of C 1s (286 eV), O 1s (532 eV), Na 1s (1072 eV), and Cl 1s (198 eV) persists; however, the Si 2p (102 eV) and the N 1s (400 eV) signals appeared and are attributed to the nanoparticles SiO 2 _APTES_120 and the amide bond formed in the nanohybrids. This is corroborated by the NIST (National Institute of Standards and Technology, Gaithersburg, MD, USA) database [ 50 , 51 , 52 ] and with the results from previous studies [ 32 , 33 , 51 , 52 ].…”
Section: Resultssupporting
confidence: 88%
“…Regarding the NH-A ( Figure 14 ) and NH-B ( Figure 15 ) spectra, the presence of C 1s (286 eV), O 1s (532 eV), Na 1s (1072 eV), and Cl 1s (198 eV) persists; however, the Si 2p (102 eV) and the N 1s (400 eV) signals appeared and are attributed to the nanoparticles SiO 2 _APTES_120 and the amide bond formed in the nanohybrids. This is corroborated by the NIST (National Institute of Standards and Technology, Gaithersburg, MD, USA) database [ 50 , 51 , 52 ] and with the results from previous studies [ 32 , 33 , 51 , 52 ].…”
Section: Resultssupporting
confidence: 88%
“…22 Meanwhile, the X-ray photoelectron spectroscopy (XPS) peaks of Ir 4f 7/2 and 4f 5/2 (Figure S4a) were estimated to be at 59.87 and 62.85 eV for Ir 25 Pt 75 and 59.98 and 62.92 for Ir 66 Pt 34 , respectively, indicative of Ir(0) as a dominated component in the nanoparticles. 23,24 The XPS spectroscopy of Pt 4f 7/2 and 4f 5/2 (Figure S4b) shows the presence of peaks at 70.13 and 73.49 eV for Ir 25 Pt 75 and 69.94 and 73.30 for Ir 66 Pt 34 , respectively, which corresponded to Pt(0). 25,26 Ir-based nanocatalysts have been previously used as OER state-of-the art electrocatalysts in water electrolysis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The XRD patterns show the presence of diffraction peaks between those of pure Ir (JCPDS file card number 46-1044) and Pt (JCPDS file card number 04-0802), revealing a uniform alloy structure of the synthesized NPs (Figure ). Meanwhile, the X-ray photoelectron spectroscopy (XPS) peaks of Ir 4f 7/2 and 4f 5/2 (Figure S4a) were estimated to be at 59.87 and 62.85 eV for Ir 25 Pt 75 and 59.98 and 62.92 for Ir 66 Pt 34 , respectively, indicative of Ir(0) as a dominated component in the nanoparticles. , The XPS spectroscopy of Pt 4f 7/2 and 4f 5/2 (Figure S4b) shows the presence of peaks at 70.13 and 73.49 eV for Ir 25 Pt 75 and 69.94 and 73.30 for Ir 66 Pt 34 , respectively, which corresponded to Pt(0). , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Theoretical methods for obtaining quantities relevant to spectrum simulation and interpretation are discussed, with emphasis on, but not limited to, numerical modelling using the Monte Carlo (MC) technique. Applications to a variety of electron beam techniques are presented such as Elastic Peak Electron Spectroscopy (EPES) Powell and Jabłonski (1999); , Reflection Electron Energy Loss Spectroscopy (REELS) Tougaard and Chorkendorff (1987); Werner (2010) and X-ray Photoelectron Spectroscopy (XPS) Werner and Powell (2021). It is shown that when appropriate analysis techniques are applied, a satisfactory level of consistency is obtained between data derived from widely different approaches, different laboratories and techniques.…”
Section: Wernermentioning
confidence: 99%